Effects of Processing Method Changes in Main Volatile Compounds of Qixue Shuangbu Prescription by Needle Trap Device Coupled with Gas Chromatography-Triple Quadrupole Mass Spectrometry. (15th December 2021) - Chen, Linwei; Jiang, Yong; Liu, Lunyuan; Bei, Chenqi; Chen, Yan; Wang, Hua; Tian, Hu; Chen, Ziduan; Wang, Qin
Abstract: Qixue Shuangbu Prescription (QSP) has been widely applied in the treatment of chronic heart failure (CHF). Previous clinical studies have found that the efficacy of processed QSP was significantly enhanced in the treatment of CHF. We have identified and analyzed the nonvolatile components before and after processing of QSP, and predicted the mechanism of synergistic effect after processing in the treatment of CHF. However, the synergistic mechanism of processed QSP caused by the difference of volatile components was still unclear. In this study, we developed a method of needle trap device coupled with gas chromatography-triple quadrupole mass spectrometry to elucidate the difference of volatile components between crude and processed QSP. The established method has been used to identify 104 volatile compounds in crude and processed QSP. The results of multivariate data showed 38 differential compounds were screened as potential markers, which would further explain the mechanism of processing synergistic effect of processed QSP. This study successfully developed the method to elucidate its processing mechanism based on the difference of volatile compositions between crude and processed QSP for the first time, and it would provide a novel analytical strategy for the impacts of different processing methods on main volatile compounds in traditional Chinese medicine.